Enhancing rural veterinary governance: coupling veterinary human resources with public attention to animal welfare - Xu, Xianhang; Liu, Hong; Yang, Jiejing; Arshad, Mohd Anuar; He, Yinglei; Chen, Qianqian; Yu, Chenshu (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aims to evaluate the coordination between veterinary human resources (VHR) and public awareness of animal welfare (PAAW) within the context of rural veterinary governance in China. It investigates how mismatches between institutional service capacity and public demand affect the development of animal health systems and human–animal relationships.MethodsThe study proposes a framework to examine the coupling between veterinary service supply and public awareness through the VHR and PAAW subsystems across 31 Chinese provinces from 2014 to 2023. It calculates annual scores using the entropy weight method, checks causal links with a panel vector autoregression (PVAR) model, and assesses coordination using the coupling coordination degree (CCD) model to assess their alignment. The relative development degree (RDD) model is further applied to evaluate development imbalances, while geographic information system (GIS) mapping visualizes spatial coordination patterns.ResultsPAAW has steadily increased in most areas, while VHR has grown more slowly. There is a unidirectional relationship where VHR significantly drives PAAW, but the reverse effect is weak. The overall CCD remains low, with most provinces showing a “VHR Lag” type, pointing to structural imbalances in supply–demand coordination.ConclusionThe study highlights the need to enhance the veterinary workforce and promote public engagement to improve animal health governance. The proposed framework offers a transferable tool for assessing implementation gaps and regional disparities in veterinary service provision, contributing to integrated approaches that connect veterinary systems, public awareness, and rural development.